Voltage constrained optimal power flow based using genetic algorithm - Yassir Asnawi; Teuku Hasannuddin (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
Voltage constrained of Optimal Power Flow (OPF) is one of several methods to minimize fuel costs while maintaining system reliability constraints. In this study, Genetic Algorithm (GA) was applied to solve the problem of OPF. Active power generator, generator-buses voltages, transformer tap and injection capacitor are used as control parameters. Effectiveness of the proposed method was tested on IEEE 30 bus system and it has been compared to other optimization of power fl ow using other methods, for example the Evolutionary Programming (EP), Differential Evolution (DE) and Particle Swarm Optimization (PSO) methods. Simulation results of the three-phase voltage profi le along the tested feeder using the proposed method provide better results than other mentioned methods. Before applying the proposed method, voltage profi le on bus 12 (load-buses) is equal to 1.058 p.u, which is beyond the acceptable limits. However, after applying the proposed method, it improved the voltage profi le at bus 12 to be within the acceptable limit, which is equal to 1.045 p.u.